2017
DOI: 10.1021/acs.est.7b03994
|View full text |Cite
|
Sign up to set email alerts
|

Certain Perfluoroalkyl and Polyfluoroalkyl Substances Associated with Aqueous Film Forming Foam Are Widespread in Canadian Surface Waters

Abstract: The presence of perfluoroalkyl and polyfluoroalkyl substances (PFASs) commonly associated with aqueous film forming foams (AFFFs) at sites without known AFFF contamination is a largely unexplored area, which may reveal widespread environmental contaminants requiring further investigation. Sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) screening for 23 classes of PFASs, followed by quantitative analysis was used to investigate surface waters from rural, urban, and AFFF-impacted sites in Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 61 publications
9
109
0
Order By: Relevance
“…Anionic PFASs present a particular environmental problem because of their resistance to biodegradation or chemical transformation and association with negative health effects . PFASs have been used in the formulations of thousands of consumer goods and are present in aqueous film‐forming foam formulations used to suppress aviation fires in training scenarios . As a result, they have contaminated surface and ground waters near thousands of airports and military installations .…”
Section: Figurementioning
confidence: 99%
“…Anionic PFASs present a particular environmental problem because of their resistance to biodegradation or chemical transformation and association with negative health effects . PFASs have been used in the formulations of thousands of consumer goods and are present in aqueous film‐forming foam formulations used to suppress aviation fires in training scenarios . As a result, they have contaminated surface and ground waters near thousands of airports and military installations .…”
Section: Figurementioning
confidence: 99%
“…In contrast, 6:2 FTSA was related in a negative fashion to ΣPFASs, suggesting particular sources and/or different environmental fate. The presence of 6:2 FTSA has been linked with industrial locations and firefighting foam impacted sites, for instance via the degradation of precursors to 6:2 FTSA present in aqueous film-forming foam formulations (D'Agostino and Mabury, 2017;Dauchy et al, 2017;Field and Seow, 2017). In addition, 6:2 FTSA itself could be biotransformed to fluorotelomer unsaturated carboxylates and…”
Section: Seasonal Variations Of Pfas Levels and Profiles In The Watermentioning
confidence: 99%
“…6 PFASs have been used in the formulations of thousands of consumer goods 19 and are present in aqueous film-forming foam formulations used to suppress aviation fires in training scenarios. 20,21 As a result, they have contaminated surface and ground waters near thousands of airports and military installations. 22,23 In 2018, the Environmental Working Group reported that over 110 million people in the United States were exposed to drinking water with PFAS concentrations above 2.5 ng L -1 .…”
Section: Introductionmentioning
confidence: 99%